How WASH Supports Social Justice in a Changing Climate:The Importance of Water - Emel Zerrouk (Revista Tecnológica)
This paper explores the relationship between social justice, the water, sanitation, and hygiene (WASH) nexus, and the centrality of water to both, all within the context of climate change. Our changing climate has placed considerable pressure on the global hydrological system, altering traditional rainfall patterns and increasing the frequency and severity of natural disasters. Ensuring adequate and sustainable access to fresh water for communities around the world is essential for human life and health.  The human right to health is seriously compromised when sanitation and hygiene services are inadequate.  It is essential that these issues are included in discussions of social justice. In conclusion, the proposed solutions to address the needs of the WASH nexus and climate adaptation overlap. Climate adaptation itself is thus seen as a human rights concern and another facet of the social justice debate.